2015
DOI: 10.4238/2015.march.13.15
|View full text |Cite
|
Sign up to set email alerts
|

Screening of rice (Oryza sativa L.) OsPR1b-interacting factors and their roles in resisting bacterial blight

Abstract: ABSTRACT. PR genes, a type of genetic marker, are constitutively expressed at background levels, while being easily inducible by pathogenic bacteria. By using a yeast two-hybrid technique, four rice (Oryza sativa L.) OsPR1b-interacting factors were screened. Homozygous plants overexpressing OsPR1b were prepared by transgenic technology. We postulated that OsPR1b may participate in the resistance signaling pathway of rice. Of simultaneous treatments with hormones and pathogenic bacteria, exogenously applying JA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…One biological process, namely, to respond to biotic stimuli (marked by the red dots in Figure 3 A), was enriched with eighteen genes ( Table S2 ), including pathogenesis-related protein 1b ( OsPR1b ) ( Figure 3 B, red dots). OsPR1b is a rice defense-related gene specifically triggered by JA/SA or blast fungus infection [ 40 , 41 ]. We further confirmed the results using a qRT-PCR assay and found that without M. oryzae invasion, the transcription level of OsPR1b was higher in ossnrk1a − 1 than in the wild type, whereas at 24 and 48 hpi with Guy11, OsPR1b was upregulated in ZH11 but not in the ossnrk1a mutant, resulting in a significantly lower OsPR1b transcription in ossnrk1a − 1 compared to that in ZH11 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…One biological process, namely, to respond to biotic stimuli (marked by the red dots in Figure 3 A), was enriched with eighteen genes ( Table S2 ), including pathogenesis-related protein 1b ( OsPR1b ) ( Figure 3 B, red dots). OsPR1b is a rice defense-related gene specifically triggered by JA/SA or blast fungus infection [ 40 , 41 ]. We further confirmed the results using a qRT-PCR assay and found that without M. oryzae invasion, the transcription level of OsPR1b was higher in ossnrk1a − 1 than in the wild type, whereas at 24 and 48 hpi with Guy11, OsPR1b was upregulated in ZH11 but not in the ossnrk1a mutant, resulting in a significantly lower OsPR1b transcription in ossnrk1a − 1 compared to that in ZH11 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…TraesCS5A02G077600 is within the interval of a fusarium head blight resistance QTL, termed Qfhs.ifa‐5AS , and is orthologous to the rice Osmotin‐like protein Os12g0569300 (National Center for Biotechnology Information, 2021; Steiner et al., 2019). TraesCS5A02G059000 is orthologous to the rice defense response gene OsPR1b, which is constitutively expressed at background levels (Luan & Zhou, 2015). Although the physical gene cluster of TraesCS5A02G046300 , TraesCS5A02G046400 , and TraesCS5A02G046500 has no known orthologs in Arabidopsis or rice, they share the additional GO terms defense response to fungus (GO:0050832), binding (GO:0005488), peptidase activity (GO:0008233), extracellular region (GO:0005576), cell wall (GO:0005618), integral component of membrane (GO:0016021), cellular component organization (GO:0016043), and cellular metabolic process (GO:0044237).…”
Section: Resultsmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted January 20, 2023. ; https://doi.org/10.1101/2023.01.18.523945 doi: bioRxiv preprint application of JA and ET significantly increased the expression level of PR1b in the seedlings. Whereas, the control sample was treated with a pathogen (Xoo) and water treatment (Luan and Zhou, 2015). M. oryzae induced the expression of PR genes such as PR1b, PR2 and PR5 (Schweizer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of JA and ET significantly increased the expression level of PR 1b in the seedlings. Whereas, the control sample was treated with a pathogen ( Xoo ) and water treatment (Luan and Zhou, 2015). M. oryzae induced the expression of PR genes such as PR 1b, PR 2 and PR 5 (Schweizer et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%